Funeral Experience in South Korea: A Phenomenological Study. (March 2022) - Park, Sungwon; Jang, Min Kyeong; Seo, Yoo-Jin; Doorenbos, Ardith Z.
Few studies of death preparation in South Korea are available. This article describes South Koreans' experiences of death and a funeral in a hospital setting to improve health care providers' ability to care for dying patients and their family. Using Colaizzi's phenomenological method, we conducted semistructured interviews with 40 South Koreans who had lost a family member in a hospital setting. Participants' statements were classified into 12 themes, 5 theme clusters, and 3 categories: (a) vagueness of funeral culture, (b) distortion of meaning in funeral culture, and (c) the need to prepare for death and process grief. Our findings are relevant to hospital-based health care providers who care for dying patients and their family. Targeted educational information could help health care providers better serve patients and family. Policy changes could improve quality of care by allowing health care providers to transition with the family from hospital units to a hospital-based funeral setting.